The Free-Time Formula - Sanders, Jeff (Ascent Audio, 2018)
The Free-Time Formula provides a real-world framework for more effective time management that helps you prioritize, focus, clarify, and go. You'll begin with a time audit to assess your current stress, strategies, and output-and the results may shock you. From there, you'll work step-by-step toward a new daily routine that will help you become the focused, efficient achiever you've been trying to be for so long. It's not about cramming more into your precious 24 hours, it's about figuring out what really matters to you, and getting the most important things done first. Every day. Never miss another big deadline, never flake on an important meeting, never be late to an appointment again. It is possible with great planning, and this book is your personal guide. Focused on action, not filler, this book is an excellent resource for those who want to achieve more, but do less. With a few simple changes, you'll find the time you've been missing and put it to more productive use.